(untitled) (Bangladesh Journal of Agricultural Research, 2010)
Key Words: Super greenfield; organo-chemical; growth and yield; wetland rice DOI: 10.3329/bjar.v34i2.5805 Bangladesh J. Agril. Res. 34(2): 323-327, June 2009